DETERMINASI BUDAYA ISLAMI DI WILAYAH PINGGIRAN KEKUASAAN BUGIS - M. Irfan Mahmud (WalennaE, 2001)
Islamic presence was recognized as transformative strength. Nevertheless, archaeological evidence indicated that Islam emergence net entirely change local culture and situation. In early times, local elements an still the most profound and energetic affirmations towards the creation of cultural forms, as found at hinterland Duri site, Enrekang, South Sulawesi. At Duri Islamic graveyards, then were no materials implementation in its basic Islamic elements; in contrary, local elements which related with Rambu Solok rites (Aluk Kamatean) are still play its dominant role, furthermore, the more concrete statues shapes reflected the strong primitive religion and, in the other hand, the weakness of Islamic culture or its teaching determination.